Prevalence of gestational diabetes in women receiving primary care: A literature review - Silva, Luiz Pedro dos Santos; Marques, Ravylla Cristina Deladio; Vieira, Marcus Vinícius Portilho; Magalhães, Claudia Christina Ribeiro Guimarães Neri de; Alcântara, Denise Soares de; Brito, Marcineide Maria Veli da Silva; Costa, Gisela Daleva; Buges, Naiana Mota (Research, Society and Development, 2023)
Introduction: Diabetes mellitus is a condition that can occur in pregnant women, due to insulin resistance due to increased production of hormones by the placenta or reduced production of insulin by the pancreas, thus increasing blood sugar levels, causing who has a positive diagnosis for the disease. General Objective: to analyze the prevalence of Gestational Diabetes seen in primary care. Method: This is a qualitative approach, this is a comprehensive literature review study that was conducted systematically. The research will be carried out by collecting information published in databases to resolve the problem presented in the study. Results: With the study, it was found that the incidence of GDM varies and is estimated between 3% and 8% of pregnant women.